2018
DOI: 10.3390/robotics7040059
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics Analysis of a Class of Spherical PKMs by Projective Angles

Abstract: This paper presents the kinematics analysis of a class of spherical PKMs Parallel Kinematics Machines exploiting a novel approach. The analysis takes advantage of the properties of the projective angles, which are a set of angular conventions of which their properties have only recently been presented. Direct, inverse kinematics and singular configurations are discussed. The analysis, which results in the solution of easy equations, is developed at position, velocity and acceleration level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…So far, most studies have focused on the kinematic issues of RSPMs, while quite a few have referred to the dynamic control of these robots. For RSPMs, several studies have been reported on a variety of relevant problems, which include modeling of workspace in joint and Cartesian space [14][15][16][17], inverse and forward kinematic analysis to obtain analytically unique real-time solutions [18][19][20][21][22][23][24][25], design and optimization [26][27][28][29][30][31][32], design and robustness [33], singularity analysis, and derivation of Jacobian matrices [34,35]. However, the constrained kinematic analysis has gone unnoticed in the literature.…”
Section: Mathematical Modeling Challenges and Control Strategiesmentioning
confidence: 99%
“…So far, most studies have focused on the kinematic issues of RSPMs, while quite a few have referred to the dynamic control of these robots. For RSPMs, several studies have been reported on a variety of relevant problems, which include modeling of workspace in joint and Cartesian space [14][15][16][17], inverse and forward kinematic analysis to obtain analytically unique real-time solutions [18][19][20][21][22][23][24][25], design and optimization [26][27][28][29][30][31][32], design and robustness [33], singularity analysis, and derivation of Jacobian matrices [34,35]. However, the constrained kinematic analysis has gone unnoticed in the literature.…”
Section: Mathematical Modeling Challenges and Control Strategiesmentioning
confidence: 99%
“…Alternatively, in [51] a solution based on spherical analytical theory was proposed. Recently, a solution based on projective angles was shown in [59].…”
Section: ) Inverse Kinematicsmentioning
confidence: 99%
“…Since the orientation of axes ûj is equal to the shape of a trirectangular tetrahedron, (59) expresses the relationship between the altitude of the tetrahedron and the lengths of its sides, which is a trigonometric property as stated in [32, p. 41]. In the isotropic pose, the planes spanned by the arcs of the proximal and distal link are oriented orthogonal to each other, which-since it holds l uv,j = l vw,j = π/2-naturally yields that base and tool axes must equally retain a right-angled configuration.…”
Section: D: Construction Of the Optimal Spm Axesmentioning
confidence: 99%
“…The use of 3D orientation ensured by the parallel spherical structure of the robot enhances the performance of active vision. In addition, detailed kinematic analysis of agile eye parallel spherical robot is presented in [27]. The design and development of a spherical parallel robot is proposed by [28], ensuring as application domain the laser pointing tasks.…”
Section: Introductionmentioning
confidence: 99%